LEADERSHIP SKILL AND MANAGEMENT PROCESS IN CENTER OF INFORMATION AND COUNSELING (CIC) AT UPPER SECONDARY SCHOOLS IN SOUTH JAKARTA CITY, INDONESIA - Utut Septi Asrianti; Arisara Leksansern (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Indonesian adolescent problems have increased from year to year based on data from the Indonesia Health Demographic Survey (IDHS). Center of Information and Counseling (CIC) is a non- formal education form which is established with particular purposes in order to help youth generation in the health and social sector. The high number of CIC does not guarantee the quality and the decreasing of adolescent health problems. This study is to examine the ability of leader and management implementation in CIC, to study problems that occurred in CIC, and find the best alternative solution to reduce these problems. Methods: The research used quantitative and qualitative method approach. Exploratory research design is used to analyze leadership skill and management in the Center of Information and Counseling. The number of population in this study is 117 students who are CIC members from 9 upper secondary schools. For the qualitative method, 13 students who are chairman and peer educator are selected to join in a focus group discussion (FGD). Results: Based on Pearson product-moment, there was a correlation between leadership skill and management process in significant level at 0.01 (r=.552). Technical skill and controlling function have the highest correlation compared with others. This finding is in line with the result of the focus group discussion. Some indicators have been founded that caused as obstacles. Some alternative solutions are given to overcome the problems and to increase the performance within CIC. Conclusion: Cooperation among all stakeholders both internal and external are needed in supporting dan developing the existence of the Center of Information and Counseling for youth generation.